Flipped learning readiness in teaching programming in middle schools: Modelling its relation to various variables - Yildiz Durak, Hatice (Journal of computer assisted learning, 2018)
The aim of this study is to investigate the effect of students' flipped learning readiness (FLR) on engagement, programming self‐efficacy, attitude towards programming, and interaction intensity in the information and technology classrooms where programming is taught with the flipped classroom (FC) model. The study group of this research, which is designed by the relational screening method, consists of 371 students studying in middle school. Structural equation model was used for the data analysis. The results of the study revealed that FLR and its indicators in the programming teaching conducted with the FC model are significant predictors of engagement, attitude, programming self‐efficacy, and interaction intensity. FLR is most strongly related to programming self‐efficacy, whereas it is most weakly related to interaction. The most striking result of this study is that the FC model is an effective option in terms of providing engagement, interaction, self‐efficacy, and learner attitude, which are the key components for the success of the instruction. It is thought that this study assists to create an awareness on the impact of FLR on students, on subjects that frame in‐class attitudes, and behaviours of students. Lay Description What is already known about this topic: Programming skills are important for the acquisition of basic skills of the 21st century. Flipped learning is an opportunity for effective programming teaching. Flipped learning readiness (FLR) has an important role in FC. However, in order for effective face‐to‐face learning to take place, it is crucial that students are able to take on the responsibility of learning outside the classroom, that is, the e‐learning readiness of their students. What this paper adds: We use FC applications in teaching programming to children. We have examined the key variables to be successful in a course involving the teaching of complex skills such as programming with FC. We brought proposals for practical education and researchers to be carried out programming instruction in FC.